2018
DOI: 10.1007/s10557-018-6822-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Inhibition of Late Sodium Current by GS967 on Stretch-Induced Changes in Cardiac Electrophysiology

Abstract: GS967 attenuates stretch-induced changes in cardiac electrophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 53 publications
5
6
0
Order By: Relevance
“…Accordingly, the regulation of increases in sarcoplasmic Ca 2+ could prevent Ca 2+ -induced alterations, such as shortening of refractoriness and focal ectopic activity, involved in the mechanisms underlying AF (Song et al, 2008;Nattel and Dobrev, 2012;Shryock et al, 2013). In previous investigations in isolated hearts, comparable effects on stretchinduced activation patterns remodeling have been described (Chorro et al, 2015;Del Canto et al, 2018). These previous observations, together with the results obtained in our study, seem to confirm the role of late sodium current in the mechanisms of stretch.…”
Section: Modification Of the Stretch-induced Effects By Ranolazinesupporting
confidence: 90%
See 4 more Smart Citations
“…Accordingly, the regulation of increases in sarcoplasmic Ca 2+ could prevent Ca 2+ -induced alterations, such as shortening of refractoriness and focal ectopic activity, involved in the mechanisms underlying AF (Song et al, 2008;Nattel and Dobrev, 2012;Shryock et al, 2013). In previous investigations in isolated hearts, comparable effects on stretchinduced activation patterns remodeling have been described (Chorro et al, 2015;Del Canto et al, 2018). These previous observations, together with the results obtained in our study, seem to confirm the role of late sodium current in the mechanisms of stretch.…”
Section: Modification Of the Stretch-induced Effects By Ranolazinesupporting
confidence: 90%
“…In fact, a reduction in tip meandering allows faster circumscription of the core of the rotor. These stretch effects are frequently associated to shorter refractoriness (Chorro et al, 2015;Del Canto et al, 2018), which is consistent with previous experimental studies in isolated rabbit hearts that showed a stretch-induced decrease in refractory periods and action potential duration (Ravelli and Allessie, 1997;Quinn and Kohl, 2016;Del Canto et al, 2018). Shortening of action potential duration has been related to stretch-induced increased intracellular Na + accumulation through several mechanisms:…”
Section: Modification Of the Stretch-induced Effects By Ranolazinesupporting
confidence: 88%
See 3 more Smart Citations